Directly cast bulk eutectic and near-eutectic high entropy alloys with balanced strength and ductility in a wide temperature range. (1st February 2017) - Lu, Yiping; Gao, Xuzhou; Jiang, Li; Chen, Zongning; Wang, Tongmin; Jie, Jinchuan; Kang, Huijun; Zhang, Yubo; Guo, Sheng; Ruan, Haihui; Zhao, Yonghao; Cao, Zhiqiang; et al.
Abstract: High entropy alloys (HEAs) usually possess weak liquidity and castability, and considerable compositional inhomogeneity, mainly because they contain multiple elements with high concentrations. As a result, large-scale production of HEAs by casting is limited. To address the issue, the concept of eutectic high entropy alloys (EHEAs) was proposed, which has led to some promise in achieving good quality industrial scale HEAs ingots, and more importantly also good mechanical properties. In the practical large-scale casting, the actual composition of designed EHEAs could potentially deviate from the eutectic composition. The influence of such deviation on mechanical properties of EHEAs is important for industrial production, which constitutes the topic of the current work. Here we prepared industrial-scale HEAs ingots near the eutectic composition: hypoeutectic alloy, eutectic alloy and hypereutectic alloy. Our results showed that the deviation from eutectic composition does not significantly affect the mechanical properties, castability and the good mechanical properties of EHEAs can be achieved in a wide compositional range, and at both room and cryogenic temperatures. Our results suggested that EHEAs with simultaneous high strength and high ductility, and good liquidity and castability can be readily adapted to large-scale industrial production. The deformation behavior and microstructure evolution of the eutectic and near-eutectic HEAs were thoroughly studied using a combination of techniques, including strain measurement by digital image correlation, in-situ synchrotron X-ray diffraction, and transmission electron microscopy. The wavy strain distribution and the therefore resulted delay of necking in EHEAs were reported for the first time. Graphical abstract: Image 1